Effect of mince washing and packaging on physicochemical quality changes of fish burger made from African catfish (Clarias gariepinus) during frozen storage - Daengprok, Dr. Wichittra; Intharapongnuwat , Watinee (Food and Applied Bioscience Journal, 2021)
African catfish (Clarias gariepinus) is a fatty fish classified as a dark muscle fish with a strong muddy odor. All these characteristics have limited its utilization in the food industry. However, washing the minced fish meat can help eliminate lipids and undesirable materials including blood, enzymes, and odorous substances such as trimethylamine oxide and formaldehyde. Effect of washing and packaging conditions on physicochemical changes of burgers made from minced African catfish was investigated during frozen storage (-18°C) for 5 months in this study. The fish burgers from unwashed mince and twice washed mince were prepared, cooked, and packed in aerobic or vacuum conditions. They were then kept at -18°C and analyzed for quality changes at 0, 1, 2, 3, 4 and 5 months. In comparison to the cooked burgers derived from unwashed and once washed mince, the cooked burgers from twice washed mince had lower moisture, fat, protein, ash contents, TBARS, total soluble proteins and cooking yield (P<0.05). After cooked, the products from twice washed mince also had a lighter color, higher shear force, lower moisture retention and lower fat retention (P<0.05). While freezing in vacuum packaging, moisture, fat and protein contents in the cooked burgers from twice washed mince decreased. It was concluded that washing mince twice and packing the cooked burger products in a vacuum condition had potential to preserve the physicochemical quality of fish burgers in frozen storage for 5 months.